2015
DOI: 10.1556/1646.7.2015.2.5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of urgent percutaneous coronary intervention on right ventricular systolic functions in non-ST-elevation acute coronary syndromes

Abstract: Abstract:Background: Although the importance of the right ventricle (RV) involvement has been known for many years in patients with ST-elevation myocardial infarction (STEMI), it is scarce in non-ST-elevation acute coronary syndrome (NSTE-ACS). Objectives: We aimed to investigate the eff ects of urgent percutaneous coronary intervention (PCI) on the RV systolic functions in patients with NSTE-ACS. Materials and Methods: Ninety-fi ve patients diagnosed with NSTE-ACS and who underwent urgent PCI were prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…One study in patients with right ventricular dysfunction after NSTE-ACS found that TAPSE and RIMP value of these patients were not significantly different before and after a succesful PCI. 21 This maybe associated with myocardial stunning after an acute myocardial infarction. RV dysfunction is reversible in most patients and permanent RV ischemic injury is very uncommon four months after acute MI treated with primary PCI.…”
Section: Discussionmentioning
confidence: 99%
“…One study in patients with right ventricular dysfunction after NSTE-ACS found that TAPSE and RIMP value of these patients were not significantly different before and after a succesful PCI. 21 This maybe associated with myocardial stunning after an acute myocardial infarction. RV dysfunction is reversible in most patients and permanent RV ischemic injury is very uncommon four months after acute MI treated with primary PCI.…”
Section: Discussionmentioning
confidence: 99%